The Birrul Walidain dalam Perspektif Al-Qur'an (Kajian Tafsir Tematik) - Mochamad Afroni; Nur Afifah (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
The research was carried out based on the verses of the Qur'an and Hadith that intersect with respecting parents. The research was conducted to find out the meaning and understanding of respecting parents in the opinion of several religious figures. The research used is library research with qualitative research type. The results of the research on the verses of the Qur'an sura an Nisa verse 36, sura Luqman verse 14, surah ash-shura verse 83 and surah al Ahqaf verse 15 found that the meaning of Birrul walidain is the devotion of a child to the verse and his mother by doing good to both of them. Later what the child does to his parents will continue to flow the reward until the afterlife.